2017
DOI: 10.1108/lm-07-2016-0058
|View full text |Cite
|
Sign up to set email alerts
|

Online library job advertisement in United Arab Emirates: a content analysis of online sources

Abstract: Purpose The purpose of this paper is to investigate and analyze library jobs advertised by higher education institutions, newspapers and job market sites in United Arab Emirates (UAE). Design/methodology/approach The paper uses summative content analysis approach for data collection, data analysis, evaluation and assessment. It reports about the accuracy of advertisements, job titles, job categories, locations and types of libraries. Findings Higher education institutions demonstrate the highest accuracy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…For their part, library schools are trying to produce skilled graduates as per market needs (Inskip, 2017). Studies of recent graduates in librarianship and information science have shown that while they have continually faced challenges in employment opportunities, possessing competency in areas such as information literacy is an advantage (Kaba, 2017;Reeves and Hahn, 2010;Fisher, 2003).…”
Section: Related Workmentioning
confidence: 99%
“…For their part, library schools are trying to produce skilled graduates as per market needs (Inskip, 2017). Studies of recent graduates in librarianship and information science have shown that while they have continually faced challenges in employment opportunities, possessing competency in areas such as information literacy is an advantage (Kaba, 2017;Reeves and Hahn, 2010;Fisher, 2003).…”
Section: Related Workmentioning
confidence: 99%
“…Such studies may also be skills-specific, as in digital curation (Kim et al, 2013) or metadata (Hall-Ellis, 2015); or they may be publication-specific, such as Wu and Li's study of reference librarian positions posted in Journal of the Medical Library Association (2008). Analyses of job announcements may also be bound by geography, as in a study of job postings by higher education institutions in United Arab Emirates (Kaba, 2017); an evaluation of job titles in Sindh Province, Pakistan (Mustafa & Ansari, 2012); or to review library information studies and information management curricula in Australia (Wise, Henninger, & Kennan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2016). Recruitment ads today are generally available online, allowing for reduced advertising costs, better access and ongoing updates; for details see Kaba (2017) and Noe et al (2017). For these reasons, vacancy advertisements were used as a source of data.…”
Section: Introductionmentioning
confidence: 99%
“…The present study involves a summative content analysis of the occurrence of soft skill and personality descriptors sought in candidates for brand manager positions. Numerous authors have used content analysis in a similar way; see, for example, recent studies focusing on librarians (Detmering & Sproles, 2012;Triumph & Beile, 2015;Kaba, 2017), logisticians (Kovacs et al, 2012), and entry-level foresters (Bettinger & Merry, 2018).…”
Section: Introductionmentioning
confidence: 99%